Lower Triassic sulphur isotope curve of marine sulphates from the Dolomites, N-Italy - Horacek, Micha; Brandner, Rainer; Richoz, Sylvain; Povoden-Karadeniz, Erwin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
6 evaporite samples from the latest Permian to the late Lower Triassic have been sampled at marine carbonate sections in the Southern Alps. The sulphur isotope ratio of the sulphate has been determined to learn about the changes of the marine δ34S ratio during the investigated period, as it is known from the literature that a profound change from depleted to heavily enriched δ34S values occurred within the Lower Triassic. The carbonates from the same sections have been analysed for their carbon isotope pattern. As the carbon isotope curve of the Lower Triassic has a very distinct pattern it enables the stratigraphic location of the evaporite layers in the section, thus it can be shown that the change in δ34S already occurred at the Dienerian-Smithian boundary or within the Dienerian. Stratification and re-mixing of ocean water are the most plausible interpretations for the observed isotope patterns.
Keywords: Lower Triassic; Ocean circulation; PTB; Stratification; Sulphur isotope